A Previously Undescribed Helotialean Fungus That Is Superabundant in Soil Under Maritime Antarctic Higher Plants - Newsham, Kevin K.; Cox, Filipa; Sands, Chester J.; Garnett, Mark H.; Magan, Naresh; Horrocks, Claire A.; Dungait, Jennifer A. J.; Robinson, Clare H. (Frontiers in Microbiology, 2020)
We report a previously undescribed member of the Helotiales that is superabundant in soils at two maritime Antarctic islands under Antarctic Hairgrass (Deschampsia antarctica Desv.). Pyrosequencing showed that up to 92% of DNA reads, and 68% of RNA reads, in soils from the islands were accounted for by the fungus. Sequencing of the large subunit region of ribosomal (r)DNA places the fungus in the Pezizellaceae or Porodiplodiaceae, with analyses of internal transcribed spacer regions of rDNA indicating that it has affinities to previously unnamed soil and root fungi from alpine, cool temperate and Low Arctic regions. The fungus was found to be most frequent in soils containing C aged to 1,000–1,200 years before present. The relative abundances of its DNA and RNA reads were positively associated with soil carbon and nitrogen concentrations and δ13C values, with the relative abundance of its DNA being negatively associated with soil pH value. An isolate of the fungus produces flask-shaped phialides with a pronounced venter bearing masses of conidia measuring 4.5–6(7) × 1.8–2.5 µm, suggestive of anamorphic Chalara. Enzymatic studies indicate that the isolate strongly synthesizes the extracellular enzyme acid phosphatase, and also exhibits alkaline phosphatase and naphthol-AS-BI-phosphohydrolase activities. Ecophysiological measurements indicate optimal hyphal growth of the isolate at a pH of 4.2–4.5 and a water potential of -0.66 MPa. The isolate is a psychrotroph, exhibiting measureable hyphal growth at -2 °C, optimal hyphal extension rate at 15 °C and negligible growth at 25 °C. It is proposed that the rising temperatures that are predicted to occur in maritime Antarctica later this century will increase the growth rate of the fungus, with the potential loss of ancient C from soils. Analyses using the GlobalFungi Database indicate that the fungus is present in cold, acidic soils on all continents. We advocate further studies to identify whether it is superabundant in soils under D. antarctica elsewhere in maritime Antarctica, and for further isolates to be obtained so that the species can be formally described.